From Bona Fides to Laba Ticība: Historical Interpretation of the Good Faith Principle in Latvian Law - Aleksejs Jelisejevs (Journal on European History of Law, 2023)
This paper focuses on a scientific analysis of the genesis and historical development of the good faith principle as a doctrinal interpretation of Latvian regulations. It is about the evolution of attitudes toward the principle of bona fides in modern legal science and case law, starting with its origins in archaic Roman law and its rediscovery by Justinian’s Corpus Juris Civilis through its application in the Western medieval ius commune and its continental renaissance in the early twentieth century, considering its limited position in the Code of Civil Laws of the Baltic Provinces to its triumph in Latvian civil law. This comparative historical study shows that a clear definition of good faith can be found through a system-historical interpretation of the good faith rule. This should help to determine the nature of subjective rights and obligations under any legal rule governing specific legal relationships.